Training on Saving and Recording Money from an Early Age with Creative Paralon Piggy Banks and Financial Literacy for Students at Muhammadiyah Kramatsari Elementary School - Niami, Nailatun; Ramadhanti, Nadina Intania; Fachrurrazi, Fachrurrazi; Ardiyansah, Feri Risqi; Arifiyanto, Muhammad (Urecol Journal. Part B: Economics and Business, 2025)
The habit of saving and recording money from an early age is an important foundation for developing a wise approach to managing finances. However, in reality, elementary school-aged children generally have limited awareness of the importance of saving and are not accustomed to tracking their expenses and income. The lack of financial education from an early age means that many children do not understand simple ways to manage their pocket money. Based on these conditions, a community service activity was designed that aims to provide basic financial training through a creative and fun approach. One of them is to introduce saving activities by making piggy banks from plastic and teaching how to record daily money simply. This activity is designed to make students more interested and to help them understand the importance of managing finances from an early age.